Husking millet and sorghum - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Small dehusking machines suitable for family use are now available. Based on the PRL models developed in Canada, these different dehusking machines can work continuously or not and are especially suited for processing small batches. They consist of...